Kinerja Outbound Logistik Susu Segar di Koperasi Peternak Sapi Bandung Utara (KPSBU) Lembang - A. Maulidina; E. Taufik; A. Atabany (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
This study was aimed to analyze the performance of the outbound logistics of fresh milk at KPSBU Lembangand quality of fresh milk during the outbound logistics process. The supply chain operation referenceanalytical hierarchy process (SCOR-AHP) method was used to analyze the logistics performance. Thequality of fresh milk observed included total solid, protein, fat, pH, specific gravity and total plate count.The obtained data were analyzed descriptively. The results showed that the performance of outboundlogistics of fresh milk at KPSBU Lembang fall into the good category (90,20%). The quality of fresh milkduring the outbound logistics process from cooperative to the dairy industry and direct consumers wasmet the quality standards of customer demand and SNI 3141.1.2011